Personality characteristics of reactance in work relations - Fourmanov, Igor A.; Kulinkovich, Tamara O. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article gives a general description of the reactance, and the situational and personal characteristics of its manifestations in human behavior. In office relations, the most visible manifestation of the reactance is a failure to comply with the intended effect after the head asks for the same action. To study the characteristics of this behavior the research was conducted with the participation of 1078 people. Methods of diagnostics of personal qualities and author questionnaire «Styles of behavior in a situation of the authorities for work relations» were used. The study showed that in a situation where the request of chef corresponds to the personal decision of the executive, people generally choose the complete subordination. However, women are significantly more likely to experience negative emotions in this case, but more often choose the subordination. Men more likely to experience positive emotions, but often use dodging or imaginary submission. Independence, personal reactance and power-leading style are influencing the choice of different kinds of disobedience.